(untitled) (Conferencea, 2022)
In this article, the need to educate an enlightened person, which is considered an important aspect determining the development of society, is revealed from a socio-philosophical point of view. Enlightened people create a space of spirituality. It was analyzed that society should educate enlightened people to build an enlightened society.